1985
DOI: 10.1093/oxfordjournals.aje.a114037
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Mumps Vaccine Efficacy

Abstract: From February 5 through April 23, 1982, 110 cases of mumps were reported among 357 students in a middle school in Ashtabula County, Ohio, an overall attack rate of 31%. Vaccine efficacy was calculated using a variety of case definitions, case surveillance systems, and vaccination-status ascertainment methods to evaluate their effects on the estimated vaccine efficacy. From data collected at the school for case ascertainment and vaccination status, clinical vaccine efficacy was initially estimated at 37%. By me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(23 citation statements)
references
References 0 publications
0
21
1
1
Order By: Relevance
“…[8][9][10] However, field studies have documented lower estimates of vaccine efficacy, ranging from 75% to 95%. 11 Antibody levels induced by the vaccine are lower than antibody levels resulting from natural infection. 8,12,13 The duration of vaccine-induced immunity is unknown, but serologic and epidemiologic data collected during 30 years of live vaccine use indicate both the persistence of antibody and continuing protection against infection.…”
Section: Vaccine Efficacymentioning
confidence: 99%
“…[8][9][10] However, field studies have documented lower estimates of vaccine efficacy, ranging from 75% to 95%. 11 Antibody levels induced by the vaccine are lower than antibody levels resulting from natural infection. 8,12,13 The duration of vaccine-induced immunity is unknown, but serologic and epidemiologic data collected during 30 years of live vaccine use indicate both the persistence of antibody and continuing protection against infection.…”
Section: Vaccine Efficacymentioning
confidence: 99%
“…Data from an outbreak of mumps in a middle school in Ashtabula County is used [17]. Among 335 children, 65 of them were vaccinated.…”
Section: An Example Of Outbreak Of Mumpsmentioning
confidence: 99%
“…[46][47][48] Outbreak-based studies, however, have reported lower efficacy rates, ranging from 75% to 95% protection from infection. [49][50][51][52] Although the duration of immunity in vaccine recipients is not completely known, serologic and epidemiologic evidence suggests that immunity persists for at least 30 years. [53][54][55][56] Adverse reactions generally are mild and uncommon after mumps vaccination.…”
Section: Currently Licensed Vaccines Virusesmentioning
confidence: 99%